Information dissemination framework for Technical Training Institutions in Kenya - Alianda, Patrick (Strathmore University, 2017)
Mobile Technology is increasingly being utilised as a tool for information dissemination and collection. Information is an important tool used in the realisation of any objective or goal set by individuals. Effectiveness of any information dissemination system is measured in terms of accessibility, timeliness as well as relevance of the information provided. Accessing Academic Information in Technical Training Institutions has been marked with numerous challenges. Key of these include under funding of these institutions and technological advancements that the Institutions have failed to embrace over a long period of time. This research provides a detailed study of the information needs of students in Technical Training Institutions in Kenya, the techniques currently used to disseminate information, how a mobile application for information dissemination can be designed, developed and tested and if the mobile application solves the challenges that are faced when using the current information dissemination techniques. Online Questionnaire were used to gather user requirements. Data analysis was done using Google analysis tools that led to the development of the Web, SMS and Mobile application to be used to disseminate information. The final prototype was an Android application that was synchronised with a backend that was very friendly and easy to use. Agile Software Methodology was used in the research. The Methodology has a series of steps that make the user much more involved in the development process. The final prototype was tested to check if functional and nonfunctional requirements were met. Testing was conducted by both the developer and potential users of the application. Last but not least the Mobile application was published on Google Play Store, SMS application hosted on both Africa is Talking Gateway with a customised name of Masai TTI and masaitti.com as the domain name. Finally a responsive Website hosted on masaitti.com to facilitate students, lecturers and support staff to be able to access timely, less costly, efficiently disseminated information.
Thesis submitted in partial fulfillment of the requirements for the Degree of Master of Science in Mobile Telecommunication and Innovation at (MSc.MTI) at Strathmore University
Keywords: Dissemination; Information Dissemination; Technical Education; Access Information